IMPLEMENTASI SISTEM PENJAMINAN MUTU SEKOLAH PADA SMPN 25 B. LAMPUNG - Hendrowati, Tri Yuni (JURNAL e-DuMath, 2016)
In globalization era, quality has related to work which produces goods and service. School is organization that produces service. In order to obtain qualified school, it needs quality of human resources such the head master, teachers, and staff. This study tries to know how is the general description of implementation schoolâs quality assurance system and quality standard decision in SMPN 25 B. Lampung. To investigate and analyze the phenomenon of research focus, the researcher used qualitative study by using three steps namely orientation, exploration, and member check. The result shows that to achieve quality school, it not only relies, on school management quality using indicator eight standard of national education but also the existence of specific experience habitually. Quality assurance system consistently has been applied since the beginning of educational school. Good management school and quality assurance system impacts on educational quality. It is influenced by some factors: a) factor of purpose, b) educator factor, c) students factor, d) infrastructure factor, and e) environmental factor. Keywords: total quality management, standard of national education, quality assurance